Sistemas de manejo e efeito residual do potássio na produtividade e nutrição do feijão-caupi - Galvão, Jessivaldo Rodrigues; Rodrigues Fernandes, Antonio; Melo, Nilvan Carvalho; Alves Silva, Vicente Filho [UNESP]; Ferreira de Albuquerque, Marcos Paulo (My University, 2013)
Cowpea [Vigna unguiculata (L) Walp] have great social and economic importance for the Para State. It grows well in areas with low precipitation and two crop cycles can be obtained annually. This study aimed to assess the effect of the residual fertilization from a previous culture (Sorghum bicolor L. Moench) and crop systems on cowpea yield and macronutrient concentration on leaves of three cowpea cultivars (BRSMilênio, BRS-Urubuquara e BRS-Guariba). The study was conducted at the UFRA. The treatments were two crop systems (minimum tillage and conventional), four levels of potassium (50, 100, 200 e 300 kg de KCl ha-1 applied to a previous sorghum culture) and the three cowpea cultivars. Treatments were organized as a three (4 x 2 x 3) factor experiment on a randomized complete block design. The soil was a yellow latosol. In each experiment plot five plants were selected to determine shoot dry matter and foliar nutrient concentration. Grain yield was determined after harvesting all plants on the experiment plot. The residual KCl fertilization affected foliar nutrient content, but did not affect shoot dry mass or yield of grain. Yield was higher in the minimum tillage system. Highest yield (1590 kg ha-1) was recorded int the cv. 'Guariba' when 100 kg of KCl ha-1 had been used in the previous crop. The highest content of leaf N and K was found in cowpea under minimum tillage system. The amount of P and Mg were higher in the conventional system whereas the amount of Ca did not change.

O feijão-caupi [Vigna unguiculata (L) Walp] tem grande importância econômica e social no Estado do Pará. Devido a desenvolver-se bem em áreas com baixa precipitação pluvial e apresentar elevada eficiência nutricional, pode ser uma alternativa como cultura de segundo ciclo anual. O objetivo foi avaliar o efeito residual da adubação potássica, realizada na cultura de primeiro ciclo de cultivo sorgo (Sorghum bicolor L. Moench), e de sistemas de manejo sobre a produtividade de grãos e teores de macronutrientes em cultivares de feijão-caupi. O experimento foi realizado no campus da Universidade Federal Rural da Amazônia (UFRA) em Latossolo Amarelo distrófico. Utilizou-se um delineamento experimental em blocos casualizados, em esquema fatorial 2 x 4 x 3, com quatro repetições. Os fatores corresponderam aos sistemas de manejo (plantio direto e convencional), doses de KCl (50, 100, 200 e 300 kg ha-1) aplicadas no cultivo anterior (sorgo) e três cultivares de feijão caupi (BRS-Milênio, BRS-Urubuquara e BRS-Guariba). O cultivar BRS-Guariba foi o mais produtivo, atingindo uma produtividade de grãos de 1590 kg ha-1, com a dose de 100 kg de KCl ha-1. Maiores teores de N e K foram encontrados nas plantas cultivadas no sistema plantio direto, enquanto teores de P e Mg foram maiores no sistema de plantio convencional. Os teores de Ca não sofreram influências dos sistemas de manejo.
Soil management systems and residual effect of potassium on yield and leaf nutrient content of cowpea
Keywords: Crop rotation; Leaf nutrient content; Tillage systems; Vigna unguiculata